Antecedentes del fundamentalismo religioso: apuntes para entender el neopentecostalismo - Barrera Rivera, Dan Abner (2023)
This article is an exposition of the origins of religious fundamentalism: its ideological and political background, where and how it arose, what its main ideas are, how it developed and what its presence has been in Central America. It is a theme that is expressedas neopentencostalism since the eighties of the twentieth century.